Organocatalytic enantioselective synthesis of beta-blockers: (S)-propranolol and (S)-naftopidil - Panchgalle, Sharad P.; Gore, Rohitkumar G.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2009)
An efficient enantioselective synthesis of beta-adrenergic blockers (S)-propranolol and (S)-naftopidil with > 98% ee using an L-proline-catalyzed alpha-aminoxylation of an aldehyde as a key step is described. (c) 2009 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (R)-(+)-alpha-lipoic acid via proline-catalyzed sequential alpha-aminoxylation and HWE olefination of aldehyde - Panchgalle, Sharad P.; Jogdand, Ganesh F.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron Letters, 2010)
An efficient enantioselective synthesis of (R)-(+)-alpha-lipoic acid is described, in high optical purity (>97% ee), using L-proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde as the key step. (C) 2010 Elsevier Ltd. All rights reserved.

Organocatalytic asymmetric synthesis of (-)-delta-coniceine based on sequential proline-catalyzed asymmetric alpha-amination-HWE olefination - Panchgalle, Sharad P.; Bidwai, Harshad B.; Chavan, Subhash P.; Kalkote, Uttam R. (Tetrahedron-Asymmetry, 2010)
An efficient asymmetric synthesis of (-)-delta-coniceine via sequential proline-catalyzed asymmetric alpha-amination and Horner-Wadsworth-Emmons olefination of an aldehyde with excellent enantiomeric excess (>99%) and high yields (overall yield 44%) is described. (C) 2010 Elsevier Ltd. All rights reserved.

Exploration of L-proline-catalyzed -aminoxylation of aldehyde to (S)-guaifenesin-related drug molecules - Panchgalle, Sharad P.; Kunte, Sunita S.; Chavan, Subhash P.; Kalkote, Uttam R. (Synthetic Communications, 2011)
[image omitted] An efficient enantioselective synthesis of (S)-guaifenesin with 99% ee using L-proline-catalyzed -aminoxylation of aldehyde as key step is described and explored for asymmetric syntheses of (S)-moprolol and (R)-methocarbamol.
Keywords: -Aminoxylation; guaifenesin; methocarbamol; moprolol; Proline